A whole body vibration perception map and associated acceleration loads at the lower leg, hip and head. Issue 7 (July 2015) - Sonza, Anelise; Völkel, Nina; Zaro, Milton A.; Achaval, Matilde; Hennig, Ewald M.
Highlights Whole body vibration severity perception rating was measured based on a Borg scale. Subjective perception ratings corresponded well with the acceleration magnitudes. The discomfort ratings might be related to resonance frequency of body parts. Machine settings can be chosen based on subject's sensation (Borg scale).